Downregulation of miR-146b-5p via iodine involvement repressed papillary thyroid carcinoma cell proliferation. (August 2020) - Pan, Yujia; Yun, Weikang; Shi, Bingshuai; Cui, Rongjun; Liu, Chi; Ding, Zhong; Fan, Jialin; Jiang, Wenqian; Tang, Jiebing; Zheng, Tianhu; Yu, Xiaoguang; Liu, Ying
Abstract : miR-146b-5p is overexpressed in papillary thyroid carcinoma (PTC) and is thought to be a related diagnostic marker. Previous studies have indicated the effects of iodine on oncogenic activation. However, the effect of iodine on the proliferation of PTC cells and the associated underlying mechanisms remain unclear. We found that miR-146b-5p was downregulated and smad4 was upregulated in patients exposed to high iodine concentration by in situ hybridisation (ISH) and immunohistochemical (IHC). NaI (10 −3 M) treatment downregulated miR-146b-5p and upregulated Smad4 in PTC cell lines. Luciferase assay was used to confirm that Smad4 is a target of miR-146b-5p. Furthermore, MTT assay and cell cycle analysis indicated that 10 −3 M NaI suppressed cell proliferation and caused G0/G1 phase arrest. Real-time PCR and Western blotting demonstrated that 10 −3 M NaI increased p21, p27, and p57 levels and reduced cyclin D1 levels in PTC cells. Our findings suggest that 10 −3 M NaI increases Smad4 levels through repression of miR-146b-5p expression, curbing the proliferation in PTC.